Discovery Science 13th International Conference, DS 2010, Canberra, Australia, October 6-8, 2010. Proceedings - Pfahringer, Bernhard.; Holmes, Geoff.; Hoffmann, Achim. (Lecture Notes in Computer Science, 2010)
This book constitutes the refereed proceedings of the 13th International Conference on Discovery Science, DS 2010, held in Canberra, Australia, in October 2010. The 25 revised full papers presented were carefully selected from 43 submissions and include the first part of the book. In a second part invited talks of ALT 2010 and DS 2010 are presented. The scope of the conference is the exchange of new ideas and information among researchers working in the area of automatic scientific discovery or working on tools for supporting the human process of discovery in science.